The Typology of Life Trajectories Among Persons with Hearing Impairment and Mobility Disabilities - Khazova, Svetlana; Adeeva, Tatiana; Tikhonova, Inna; Shipova, Natalia (Social Welfare: Interdisciplinary Approach, 2018)
The article analyzes the sociological and psychological approaches to the understanding of the “life trajectory” phenomenon. The “life trajectory” and “way of life” notions are compared as well as categorical features which describe life trajectories were pointed out, the most important of which are: sociocultural determinism, dynamism, eventfulness, continuity, narrativity, typical nature as the evidence of the similarity between trajectories in a particular group of people within specific time and space frame. The authors have suggested a novel approach which enables to identify objective facts making up one’s life trajectory and their subjective interpretation. The empirical data allowed to recognize two variations of life trajectories that were code-named the “hypersthenic” (highly positive appraisal is prevalent) and “hyposthenic” (pessimistic appraisal of life events is prevalent) ones. It led to the conclusion about both theoretical and methodological complexity to study disabled persons’ life trajectories.
Keywords: life trajectories; way of life; adults with disabilities (disabled-since-childhood adults); the typology of life trajectories; hearing impairment; mobility disabilities